1961
DOI: 10.1152/jappl.1961.16.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral hypoventilation produced in dogs by occluding one pulmonary artery

Abstract: Temporary unilateral pulmonary artery occlusion resulted within 1 minute in a shift of tidal volume away from unperfused lungs in 14 anesthetized closed-chest dogs. The shift of ventilation was caused by bronchoconstriction following the decrease of CO2 on the occluded side. It was prevented by inhalation into that side of 6% CO2 in air, isoproterenol aerosol or 100% N2, but not by atropine or vagotomy. Airway resistance on the occluded side was doubled, and compliance fell 25%. Functional residual capacity fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
2
7

Year Published

1961
1961
2006
2006

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(84 citation statements)
references
References 0 publications
6
69
2
7
Order By: Relevance
“…In the distal segments the same contraction would cause widespread closure of the terminal airways with a fall in ventilated lung volume and CL. This appears to be the "unknown mechanism" (41) that produces a shift of ventilation toward the unaffected parts of the lungs, as demonstrated by fluoroscopy (42) and bronchospirometry (43) and by means of a ballooncatheter (44,45).…”
Section: Methodsmentioning
confidence: 99%
“…In the distal segments the same contraction would cause widespread closure of the terminal airways with a fall in ventilated lung volume and CL. This appears to be the "unknown mechanism" (41) that produces a shift of ventilation toward the unaffected parts of the lungs, as demonstrated by fluoroscopy (42) and bronchospirometry (43) and by means of a ballooncatheter (44,45).…”
Section: Methodsmentioning
confidence: 99%
“…Actually, the increase in dead space per se does not induce hypoxemia. For this reason, hypoxemia is attributed to a significant alteration of the V A /Q ratio (3,5,10,14,15,17,25), with alveolar ventilation being slightly increased but with perfusion being markedly increased.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Levy and Simmons (15) observed that in PE there is a partial auto-regulation of the alveolar ventilation and perfusion at the lobar and segmental levels in order to maintain the equilibrium of the V A /Q (4,16). This phenomenon has only recently been confirmed with technology based on positron emission tomography scan that quantifies the redirection of the ventilation to alveoli with maintained perfusion, called effective or regional alveolar ventilation (V A eff) (14,17,18). Most studies attribute the redirection of alveolar ventilation to regional bronchoconstriction induced by alveolar hypocapnia (14,15,17,19,20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PEEP effect on tracheomotor tone depends on the resting level of airway smooth muscle tone. Severinghaus et al 12 suggested that local mechanisms control airway smooth muscle tone, and hence ventilation: perfusion matching. Our data suggest that systemic acid-base balance also contributes to the magnitude of the tracheomotor response to PEEP.…”
Section: Discussionmentioning
confidence: 99%